Subclinical anthracycline- and trastuzumab-induced cardiotoxicity in the long-term follow-up of asymptomatic breast cancer survivors: a speckle tracking echocardiographic study. Issue 9 (27th April 2010) - Ho, Emily; Brown, Angela; Barrett, Patrick; Morgan, Roisin B; King, Gerard; Kennedy, M John; Murphy, Ross T
Abstract : Objective: To examine the long-term effects of standard chemotherapy on myocardial function in asymptomatic breast cancer survivors using two-dimensional speckle tracking echocardiography. Methods: Seventy women (chemotherapy group) aged 54±8 years who had received anthracycline treatment with (n=19) or without (n=51) adjuvant trastuzumab up to 6 years previously, and 50 female controls were studied. Left ventricular systolic (ejection fraction (EF%), peak systolic myocardial excursion, (Sm)) and diastolic (peak mitral E and A velocities, six-point average of mitral annular E′ velocities) function, 2D global and regional longitudinal and radial strain were determined using standard 2D Doppler and tissue Doppler echocardiographic methods and speckle tracking software. Results: Despite normal EF% (62±4% vs 60±3%, p=0.051) the chemotherapy group had reduced E/A ratios (0.9±0.3 vs 1.1±0.3, p=0.003), global E′ (10.2±2 vs 11.2±2.3, p=0.036), global Sm (9.0±1.3 vs 9.6±1.3, p=0.029) and global longitudinal 2D strain (−18.1±2.2 vs −19.6±1.8, p=0.0001) in comparison with controls. In 18 (26%) of the chemotherapy group, global longitudinal strain was below the lower limit of the control group. Cigarette smoking was a negative predictor of longitudinal strain, but only in the chemotherapy group. Radial strain did not differ significantly between the two groups. There were no significant differences in EF%, global Sm and longitudinal strain between trastuzumab-treated individuals and controls. Conclusions: Subclinical systolic and diastolic myocardial abnormalities were present in asymptomatic breast cancer survivors up to 6 years after standard chemotherapy. Cigarette smoking had a negative effect on longitudinal strain in these individuals. Adjuvant trastuzumab treatment did not appear to have an additive adverse impact on myocardial function in the medium–long term.